Alveolar distraction osteogenesis for oral rehabilitation in reconstructed jaws - Cheung, L.K.; Hariri, F.; Chua, H.D.P. (Lippincott, Williams & Wilkins, 2011)
Purpose of review To present a literature review of alveolar distraction osteogenesis (ADO) for reconstructed jaws, with emphasis on indications, critical surgical factors, protocols and complications for oral rehabilitation of reconstructed jaws. Recent findings The defects in jaw result mostly from malignancy, benign tumor or gunshot injury. Jaw reconstructions were performed mostly by vascularized fibula graft. Alveolar distraction was primarily indicated to correct vertical discrepancy between the reconstructed region and residual ridge in order to achieve adequate height of the transplanted bone prior to implant placement. The vertical bone height gained ranged from 6 to 15 mm. The most common complications reported were infections and distractor malalignment. Summary This review reveals few numbers of case series on this topic. However, ADO in reconstructed jaws can produce consistent evidence of bone regeneration, with stable augmentation results clinically, histologically and radiographically, thus making it a predictable surgical procedure prior to oral implant rehabilitation.